Training load in pre-puberal female artistic gymnastics - Burt, L. A.; Naughton, G. A.; Higham, D. G.; Landeo, R. (Science of Gymnastics Journal, 2010)
An understanding of the multiple factors affecting young gymnasts is required to assist in optimizing performance and injury prevention. We aimed to determine the effects of participation level (international and national level gymnasts), apparatus (beam and floor) and training phase (pre-competition and competition) on estimates of training load in 25 female artistic gymnasts (mean age 9.5, SD = 1.6 years, training age 1.9, SD = 0.7 years). Video analysis was used to determine frequency of observed gymnastic-specific movements involving estimates of ankle and wrist impacts, landings, balance-related skills, and rotations. To further estimate training load, 16 gymnasts performed sport-specific skills, on a portable force platform. Results from a series of ANOVAs showed training load differences between the two groups. Compared with national level gymnasts, international gymnasts demonstrated increased hours of training, and a greater frequency of observed impacts (independent of time). Differences were also observed between the two phases of periodised training in both participation levels however, international gymnasts followed a more refined training program. No between group differences were evident for ground reaction forces on the beam and floor. Periodisation and training load should be monitored objectively to assist in ensuring the longevity of athletes and ideally minimising injury risk.